(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study under the title "A STUDY ON WHETHER ACCEPTANCE/NON-ACCEPTANCE OF DIGITAL PAYMENT METHODS IS AFFECTING BUSINESS WITH SPECIAL REFERENCE TO THRISSUR DISTRICT OF KERALA STATE” was conducted to find out how vital digital payments have become in the success of a business. The population of the study was all small-scale merchants and retailers in the Thrissur district out of which a sample of 100 units was derived by judgment sampling technique. The research followed a descriptive research design and the primary data was collected through the administration of a questionnaire. The secondary data was collected through journals, newspapers, books, and the internet. The study was conducted on merchants and street vendors from different categories of business. From the data thus collected a chi-squared test was conducted to find if there is any relation between acceptance of digital payments and growth in business. The test resulted in a chi-squared value of 11.949 and p-value of .017734 which implies that the result is significant and that the null hypothesis "H0: Acceptance/non-acceptance of digital payment methods has no effect on business" is rejected and the alternative hypothesis "H1: Acceptance/non-acceptance of digital payment methods has a significant effect on business" is accepted.